HUBUNGAN KEKERABATAN FILOGENETIKA KULTIVAR PISANG DI INDONESIA BERDASARKAN KARAKTER MORFOLOGI - Amin Retnoningsih (Floribunda, 2011)
Amin Retnoningsih. 2011. Phylogenetic relationship of cultivated bananas in Indonesia based on morphological characters. Floribunda 4(2): 48–53. — Indonesia has high biodiversity of cultivated bananas. This research objective is reveal the phylogenetic relationship of cultivated bananas in Indonesia based on morphological characters. This research analyzed 2 groups which are consist of ingroup namely 9 banana accessions on genome groups AA, 9 AAA accession, 8 AAB accession, 8 ABB accession, and 2 BB accession, and the other group is outgroup which representated by 2 wild bananas. The method of this research usingCladistic program Phylogenetic Analysis Using Parsimony (PAUP) version 4.0, it used to produce phylogenetic trees. The study branches are tested by bootstrap 100 times. The results show that morphological characters have parallel homoplasm which can be seen from the low CI score by 0.275. Taxon tested are species and under species level (Musa spp). In general, there is no difference on changes of morphological characters in each clade. The clade consist of Boi accession (ABB), Klutuk Wulung (BB) and Klutuk (BB) separated from ingroup clade because they have differences of morphological characters from the others. They are showed by high bootstrap score: 98%. The Klutuk Wulung and Klutuk are predicted to have close phylogenetic relationship with the wild Musa balbisiana (BB).